CONVERTING A DESERT BUGGY INTO SOLAR ELECTRIC VEHICLE - Osman, Ahmed H.; Massoud, Magdy. M. (European Scientific Journal, ESJ, 2013)
The renewable energy became an essential demand for today’s world life for all its importance in decreasing pollution and keeping our environment clean. The solar car is a step in saving our environment and energy resources. New project (supported from King Abdulaziz & his Companions Foundation for the Gifted and Technical & Vocational Training Corporation, KSA) is targeted to build a solar electric vehicle. The project was designed for talented students in the field of Vehicles & Engine Technology in Saudi Arabia. We initiated a program for one month duration, which includes different activities in designing, soldering, suspension, steering, electric motors, solar cells and batteries. The aim of this program is to prepare the students to cooperate as a team in achieving the production of the solar electric vehicle. Starting from a very cheap desert buggy, the new solar vehicle is assembled in innovative manner with used material and component. The solar vehicle is assembled in the workshop of Riyadh College of Technology. The solar vehicle is successfully assembled, operated, tested and ran as fast as 50 km/hr for 3 hours with fully charged batteries. The solar panels will continue charging the batteries. On the other hand, the batteries can also be charged using regular 220 AC Volt. The solar cells extends the running distance by about 40%